Design and Development of NeuroAR Media in Nervous System for High School Biology Learning - Annisa Syafigha Putri; Yanti Hamdiyati; Eni Nuraeni (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2025)
Nervous system material is often considered difficult by students due to its abstract and complex nature. Augmented Reality (AR) emerges as a technology capable of effectively visualizing objects, particularly in presenting 3D objects interactively and dynamically for abstract and complex concepts. This study aims to develop AR based learning media in the nervous system material that is feasible for use in classroom learning through interactive and dynamic visualizations. The type of research used is research and development (R&D) with research steps referring to the 4D Models, which include the stages of Define, Design, Development, and Dissemination. This study was limited to the Development stage because focusing solely on developing and validating the feasibility of NeuroAR without including the Dissemination stage. This study includes an explanation of the identification of learning challenges, and potential use of AR, which is conducted through teacher interviews, classroom observations, and student questionnaires. Then, it explains how planning the content structure, visualizing 3D organs and bioprocesses, designing audio elements, and designing AR-based learning activities and explains how the development stage includes media development using Unity3D, Assemblr Edu, Blender, Canva, and Solidworks. Validation by media and material experts, and readability test by students. The result of this research is the producted of NeuroAR media on nervous system material that has been declared feasible and valid for use in learning, as indicated by the results of material and media expert validation categorized as very valid and the readability test by students which showed a positive response.